Central Nervous System Vasculitis as a Systemic Manifestation of Systemic Lupus Erythematosus: A Case Report - Bastidas-Chacón, Natalia (2023)
Systemic lupus erythematosus is an autoimmune disease with a wide variety of clinical manifestations, including those resulting from central nervous system involvement, known as neuropsychiatric manifestations. We present the case of a 20-year-old female patient diagnosed with systemic lupus erythematosus, who was admitted to the emergency department due to the sudden onset of monoparesis and hypoesthesia in the right upper limb. Magnetic resonance angiography revealed a segmental decrease in the caliber of multiple arteries in the anterior and posterior cerebral circulation, ultimately leading to the diagnosis of central nervous system vasculitis secondary to her underlying pathology. This prompted timely management, resulting in an improvement in her functional status. Recognizing the neuropsychiatric manifestations of lupus is crucial for establishing adequate treatment, as the prognosis of the disease depends on the extent of central nervous system involvement, which, in turn, may be influenced by the timing of treatment initiation.